Research Progress on the Immunological Correlation Between Papillary Thyroid Carcinoma and Hashimoto’s Thyroiditis - Digui Fang; Limei Zhou; Biao Zheng (Journal of Immunology Research)
In recent years, a growing body of evidence has suggested a correlation between Hashimoto’s thyroiditis (HT) and the onset and progression of papillary thyroid carcinoma (PTC). However, the mechanism underlying the relationship between HT and PTC remains incompletely understood. This review discusses the literature on the correlation between PTC and HT and summarizes the research concerning the immunological interplay between these two conditions. It also delves into tumor-associated cells (such as CD8+ T cells), tumor-associated macrophages (TAMs), regulatory T cells (Tregs), and cancer-associated fibroblasts (CAFs), alongside other tumor-associated factors, including interleukins (ILs), interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), and hypoxia-inducible factor-1 (HIF-1), highlighting their roles in the interaction between PTC and HT. We also explore the strategic direction of immunotherapy in thyroid malignancies, particularly PTC with HT, and propose novel targeted immunotherapies for advanced thyroid cancer.